What is the Basis of Human Rights? - Nekrašas, Evaldas (Problemos, 2000)
The traditional understanding of human rights as divine or inborn is out of fashion today. Positivism succeeded in undermining it. Yet the positivist reduction of the law to positive law, and the identification of human rights with positive rights granted by the state makes human beings too much dependent upon states and their laws. The positive school of law must of necessity acknowledge that these rights are determined by legal norms approved by state authorities. Yet from the contemporary moral stance this is unacceptable. We are inclined to treat human rights as higher standards than state’s legal norms. Hence we need to prove that human beings really have specific rights even if a state does not grant them to its citizens and residents. How is it possible to do this without invoking metaphysical or religious notions? It seems that the simple idea that human beings have those rights which a community recognizes as appertaining to them, is a way out of the situation. Historically, public acceptance of the very idea of natural rights was closely linked with specific metaphysical or religious notions. They played an important role in the process of transforming - in the public perception - specific ideals into specific rights. Now this process has reached a rather advanced stage. This empirical fact enables us to elide metaphysical and religious notions when discussing the reasons for respecting human rights. We may dispose of these notions like the Wittgensteinian ladder and limit ourselves to the examination of what members of a community believe their rights to be. In this case the most important problem becomes delimiting the boundaries of the community, whose members’ human rights are upheld or infringed, and the relation of these boundaries to the borders of the state. A person may be a member of many communities at once. Originally the notion of human rights was accepted by a small community (or communities). While questions regarding the status or identity of those communities may be fascinating, for us they are rather irrelevant. At present, however, there is more than one reason to claim that the broadest community which acknowledges that human beings have the right (at least) of life, liberty and property comprises all humankind. And although the acknowledgment of these rights is still far from being sensu stricto universal, no state has the right to ignore them. In this way it is possible to maintain that in spite of the fact that the notion of natural and universal human rights cannot be convincingly justified along metaphysical or religious lines, such rights exist indeed, and are superior to the rights which a specific state grants or fails to grant to its nationals.